Bases de Schiff como potenciais agentes leishmanicidas contra Leishmania chagasi in vitro - Coelho, Laiza Gabriela Gavioli (Universidade Federal de São Carlos, 2016)
The neglected diseases are a group of diseases with a higher incidence in poor regions and tropical or subtropical climate. The leishmanioses are listed in this group of diseases, which may present themselves in two ways: tegumentary leishmaniasis or Visceral Leishmaniasis (VL). The VL in the new world has as the etiology Leishmania chagasi, which is transmitted by the bite of the sandfly, especially Lutzomya longipalpis. There are some medications used for the treatment of VL, however, still there are recurrence rates and high mortality. In addition to the severe side effects related to these therapies, as Nephrotoxicity, hepatotoxicity and cardiotoxicity. Not long ago it was developed the amphotericin B encapsulated the Liposomes, associated with mild side effects, however still with an onerous cost, being hard to use in regions devoid of resources. In this work we aim to evaluate the activity of 15 compounds with Schiff bases complexed or not the metals (copper, nickel, zinc and iron), to inhibit promastigotes of Leishmania chagasi in vitro, as well as the cytotoxicity of these front of macrophages and fibroblasts in vitro. For tests with the promastigotas 24 hour incubation was carried out to evaluate the feasibility of resazurin method was used. To evaluate the cytotoxicity of compounds was incubated for 24 or 48 hours, using the colorimetric method with MTT. Of the 15 compounds evaluated, 11 showed good activity in inhibiting the promastigotas in the concentrations tested, the cytotoxicity performed with these 11 compounds. Copper complexes (D1, D2, D3) presented best activities when compared with their respective free ligands. However, they also showed cytotoxicity. The compounds complexed with iron (C1 and C3) also showed activity against the promastigotes, showing no or low cytotoxicity front cells, except the C1 that presented certain toxicity front of macrophages. The Methoxy group was what showed best activity when compared to the other free ligands. Generally the free ligands, without metals, were the ones who presented lower cytotoxicity.
Keywords: Leishmaniose visceral; Metal pesado; Promastigotas; Resazurina; Visceral Leishmaniasis; Heavy Metal; Leishmanicida; Promastigotas; CIENCIAS BIOLOGICAS